(untitled) (Tongkonan: Jurnal Pengabdian Masyarakat, 2024)
Education and screening for color blindness are activities that should be carried out early so that further treatment can be obtained. This can be done through a doctor’s examination. However, Bonetambu Island is one of the remote areas in Makassar City that requires sea access to reach Makassar City and does not have proper facilities, such as an eye doctor. This is the basis for implementing activities at SDI Barrang Caddi II, Bonetambu Island, which is the only elementary school on Bonetambu Island. This activity was carried out in September 2023. The results of the activity showed that there were no students who experienced color blindness. The implementation of this service involved providing counseling or education about the sense of sight and, at the same time, conducting color blindness screenings using the Ishihara method. The results of this service activity show that all students who participated in the activity received education about eye disorders, and none of the participants experienced color blindness.